Decoding the transcriptome from bulk RNA of infection-naïve versus imprinted patients with SARS-CoV-2 Omicron B.1.1.529 - Sissy Therese Sonnleitner; Samira Walder; Eva Hinterbichler; Ludwig Knabl; Roswitha Poernbacher; Gernot Walder (Microbiology Spectrum)
ABSTRACT Total RNA-seq allows for the comprehensive detection of differentially expressed genes (DEGs), providing insight into immune responses during infection. In this study, we addressed the question of whether total RNA-seq can detect differences in gene expression and, therefore, immune responses between infection-naïve and imprinted patients. By sequencing all DEGs in the acute phase of a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron B.1.1.529 infection, we examined the biological processes that characterize patients with different immune statuses. We differentiated between infection-naïve individuals (Group A), individuals imprinted by prior SARS-CoV-2 infection (Group B), and individuals first imprinted by vaccination (Group C). Infection status was confirmed by SARS-CoV-2-specific PCR; viral strain identification was performed via melting curve analysis; and immune status was assessed by chemiluminescent immunoassay. Our findings revealed significant transcriptomic differences between the study groups. Infection-naïve individuals exhibited the highest number of differentially expressed genes (1,526 DEGs), compared to 27 in previously infected individuals and only seven in vaccinated individuals. A key aspect of this difference was the expression of interferon-stimulated genes, which showed a progressive decline from infection-naïve to previously infected to vaccinated individuals. Notably, Group C displayed almost no upregulated genes but instead exhibited significant downregulation in pathways related to DNA metabolism. A key strength of our study is the inclusion of infection-naïve individuals at a time when most of the population had already been exposed to SARS-CoV-2. This rare opportunity allowed us to characterize the primary immune response to Omicron B.1.1.529 in infection-naïve individuals and compare it to immune responses shaped by prior infection or vaccination. The clear differences in gene expression between these groups highlight how prior exposure influences immune activation during acute infection.IMPORTANCEUnderstanding how prior immune imprinting through infection or vaccination influences the transcriptomic response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is crucial for optimizing vaccine strategies and predicting immune outcomes in future pandemics. A unique strength of our study is the inclusion of infection-naïve individuals at a time when most of the population had already been exposed to SARS-CoV-2. This rare opportunity allowed us to characterize the primary immune response to Omicron B.1.1.529 and compare it to responses shaped by prior infection or vaccination, providing valuable insights into how immune imprinting influences transcriptional activation during acute infection.